PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS V SD NEGERI 001 UKUI KECAMATAN UKUI - Marni Yusuf (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low mathematics learning outcomes of students. Out of 28 students, only 14 students achieved learning mastery, with an average score of 65. Therefore, the researcher conducted a classroom action research by applying the demonstration method. This research was carried out in two cycles. The data collected included teacher activities, student activities, and students’ mathematics learning outcomes. The research was conducted in class V of SD Negeri 001 Ukui, Ukui District. Based on the results of the research, the data showed that students’ learning outcomes as well as teacher and student activities increased in each cycle. This was evidenced by the improvement in teacher activities: in Cycle I Meeting I, the score obtained was 13 (46.42%); in Cycle I Meeting II, the score increased to 18 (64.28%); in Cycle II Meeting I, the score increased to 20 (71.42%); and in Cycle II Meeting II, the score reached 26 (92.85%). Student activities also increased in each cycle. In Cycle I Meeting I, the score obtained was 12 (42.85%); in Cycle I Meeting II, the score increased to 19 (67.85%); in Cycle II Meeting I, the score increased to 21 (75.00%); and in Cycle II Meeting II, the score reached 25 (89.85%). Furthermore, students’ mathematics learning outcomes improved in each cycle. The preliminary data showed that only 50% of students achieved mastery, with an average score of 65. In Cycle I, mastery increased to 70% with an average score of 69.25. In Cycle II, classical mastery reached 85% with an average score of 74.50. It can be concluded that the application of the demonstration method can improve mathematics learning outcomes of fifth-grade students at SD Negeri 001 Ukui.